ВИЗНАЧЕННЯ СКЛАДОВИХ ВТРАТ АКТИВНОЇ ПОТУЖНОСТІ В ДАЛЬНІЙ ЕЛЕКТРОПЕРЕДАЧІ ЗМІННОГО СТРУМУ - Кацадзе, Т.Л.; Чижевський, В.В.; Буслова, Н.В.; Черкашина, В.В. (Інститут електродинаміки НАН України, Київ, 2022)
The components of active power losses in long-distance AC power transmission are investigated. It is shown that in the modes of low and medium loads the main share of losses are corona losses. The imperfection of the current method of determining the corona power losses, which are climatic in nature, determines the method of separating these losses from the total after calculating the load power losses. A four-component formula for determining the load losses of active power is obtained. It is shown that to clarify the calculation model it is necessary to take into account the actual temperature of the wire, taking into account changes in weather conditions along the route of the line. The results of calculation of components of active power losses in the 750 kV overhead transmission line "Zakhidnoukrainska-Vinnytska" during the day of September 13, 2021 are given. References 9, figures 4, tables 3.